Perencanaan Karir Siswa MAN 1 Nganjuk Kelas XI - Ulfa Madina Fitrayani; Muhammad Sholihuddin Zuhdi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Career is the work-related activities and achievements obtained by an individual and the jobs handled during working life. In the career planning process, students' skills and talents are used in accordance with career planning goals. Research that uses qualitative research with a case study approach. Qualitative research is research produced using written and spoken words, as well as activities that can be studied. The methods used in collecting data are observation, interviews and documentation. Which was carried out at the MAN 1 Nganjuk location, with primary data from class XI students and secondary data from MAN 1 Nganjuk bk teachers. The research carried out aims to look at the career planning of MAN 1 Nganjuk students based on the aspects that students need in planning their careers. The resulting research shows that MAN 1 Nganjuk class XI students have planned their careers according to the students' interests, talents and potential, based on aspects of knowledge, attitudes and skills. To be able to determine the right career choice, students must have the skills to determine adequate career planning because career choices can determine future success.